VIRULENCE OF HELICOBACTER PYLORI IN PATIENTS WITH GASTROPATHY IN RHEUMATOID ARTHRITIS (Conferencea, 2023)
Helicobacter pylori (H.pylori) is a gram-negative flagellar spirally twisted, microaerophilic bacterium that has urease activity, it is characterized by colonization of the gastric mucosa [1]. With H.pylori chronic gastritis, gastroduodenal ulcers, stomach tumors, MALT-lymphomas are often aggravated [2]. In addition, the prevalence of H.pylori often associated with regional characteristics, social and economic factors, age and ethnicity. H.pylori. more common in developing countries and less common in developed. There are studies related to the detection of H.pylori. bacteria, however, as a development of the development of gastroduodenal diseases, not fully understood [3]. In addition, it is known that the virulence properties and genetic characteristics of the pathogen are manifested in the form of H.pylori comorbidities [4, 5].